Strengthening innovative work behaviour through HR practices in Malaysia’s oil and gas industry: A conceptual study - Mahzair, Ahmad Muaz; Mat Noor, Ahmad Nizan; Md Sabri, Sabiroh (International Journal of Accounting, Finance and Business, 2025)
Innovative Work Behaviour (IWB) is increasingly critical for organisations navigating competitive and technology-intensive industries, such as oil and gas, where operational resilience and continuous improvement are key to long-term success. Despite substantial investment in advanced technologies, many organisations struggle to convert these assets into employee-driven innovation, highlighting a gap in the organisational practices that support innovation. In the Malaysian oil and gas sector, this gap is particularly evident. Human Resource (HR) practices are widely acknowledged as strategic tools to build innovation capabilities by enhancing employee ability, motivation, and opportunity. However, the consistent underperformance in innovation outcomes suggests that the application of these HR practices may not be fully optimised within this context. This conceptual study aims to explore how four key HR practices, namely training and development, performance management, rewards and recognition, and employee engagement, influence IWB among employees in petrochemical operations. Guided by the Ability-Motivation-Opportunity (AMO) theory and Social Exchange Theory (SET), the study employs a narrative literature review methodology to synthesise recent scholarly findings. Based on this review, the paper proposes a conceptual framework that outlines the pathways through which HR practices foster innovative behaviours at the employee level. The framework offers theoretical insight into the mechanisms linking HRM and innovation, while also presenting practical guidance for HR professionals in high-compliance sectors. By aligning HR practices with industry-specific demands, organisations can better activate employee potential and translate it into meaningful innovation.